Peran Guru PAK sebagai Teladan Bagi Peserta Didik di Era Globalisasi - Yosika Rodina Anin; Marisa Aulia Gea; Difly Praise Malelak (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
In the era of ever-growing globalization, the role of Agana Kristen education teachers as role models for students has become very crucial. This article discusses the significance of this role in shaping the character and moral values ​​of students amidst global change. PAK teachers must be pillars of integrity, morality and diversity for students, becoming inspiring examples in facing the complexity of today's challenges. This article describes key aspects of the role of PAK teachers as role models, including moral education, character formation, and instilling Christian religious values. In the era of globalization, where information is widely spread and diverse, PAK teachers have the responsibility to guide students so that they are able to understand and absorb universal values, while maintaining the integrity of local values ​​which are part of the nation's identity.